GAMBARAN PENERIMAAN DIRI PADA PEREMPUAN YANG MENGALAMI PENYAKITBEBAINAN DI BALI - Ni Made Prima Kusuma Dewi; I Gusti Ayu Diah Fridari (Jurnal Kesehatan, 2024)
Balinese people have high religious values and still believe in supernatural powers. Bebainan comes from the word bebai which means disease. Bebainan can be interpreted as a disease or a sick condition of a person caused by non-medical matters so that a person who is bebainan feels several symptoms such as unconsciousness, feeling of fear, discomfort, pain in the abdomen, emotional sensitivity and changes in mood. Researchers can find out the symptoms felt by someone who is experiencing a bebainan through interviews. This study aims to find out how the process of self- acceptance of women who experience bebainan. In this study, the researcher used a qualitative method with a case study approach with the criteria of female respondents in the age range of 21-40 years and respondents who had or were experiencing a bebainan. The sampling technique used is purposive sampling. The results of this study found that the first respondent experienced a bebainan in 2022, while the second respondent felt a bebainan in 2019 and the respondent again felt a bebainan in 2022. The response was given by the surrounding environment as long as the respondent experienced a bebainan such as babysitting and expanding. Then personal responses also appeared within the respondent such as feelings of fear, avoidance, feelings of discomfort and the respondent accepted the bebainan experience that the respondent felt. Based on the results of this study, it can be concluded that respondents who experience bebainan illness will accept themselves if the respondent gets positive support from their environment. In addition, it can be concluded that respondents who experience bebainan illness further increase their spirituality where respondents pray more often after experiencing bebainan and more grateful for what happened to him.